Strategic sport management : sustainability of sports clubs - Varmus, Michal; Kubina, Milan; Adámik, Roman (Contributions to management science., 2021)
"Sport, and in particular the sporting environment, has undergone significant changes in recent decades. The social significance and commercialization of sport; the use of new technologies and organizational structures; and the involvement of various stakeholders matter more today than ever before. This book addresses the key influence of stakeholders in particular on the activities of sports organizations, taking into account certain territorial differences around the world, but also within Europe. The authors explain the key characteristics of the management of sports organizations as opposed to other organizations. These include the strategic management and setting of long-term goals such as sporting success, sustainable funding, youth training, and community building. The authors present a strategic model for these goals and stakeholders in the context of sport, together with research-based case studies in which the critical factors in the strategic management of successful and unsuccessful sports organizations are identified"- Resumé vydavatel